UNDERLYING PROBLEMS OF SHIP RECYCLING INDUSTRIES IN BANGLADESH AND WAY FORWARD (Journal of Mechanical Engineering, 2013)
Ship recycling has been playing as a catalyst role for the economy of Bangladesh by supporting steelindustry, shipbuilding industry and other industries and it has also been generating huge employments for thecountry. But, existing problems of this industry in terms of safety, health and environmental issues bringnegative image for the country sometimes. This paper is aimed to identify the underlying problems of shiprecycling industry at first and then analyze the nature of the problems to make it helpful overcoming theobstacles. A brief overview has been given focusing recent development of this sector. A guideline has been putforward to overcome all these problems in order to hold a strong position in the world ship recycling.DOI: http://dx.doi.org/10.3329/jme.v42i1.15932